Microphysiological heart–liver body-on-a-chip system with a skin mimic for evaluating topical drug delivery. Issue 4 (23rd January 2020) - Pires de Mello, Camilly P.; Carmona-Moran, Carlos; McAleer, Christopher W.; Perez, Julian; Coln, Elizabeth A.; Long, Christopher J.; Oleaga, Carlota; Riu, Anne; Note, Reine; Teissier, Silvia; Langer, Jessica; Hickman, James J.
Abstract : Body-on-a-chip in vitro systems are a promising technology that aims to increase the predictive power of drug efficacy and toxicity in humans when compared to traditional animal models. Abstract : Body-on-a-chip in vitro systems are a promising technology that aims to increase the predictive power of drug efficacy and toxicity in humans when compared to traditional animal models. Here, we developed a new heart–liver body-on-a-chip system with a skin surrogate to assess the toxicity of drugs that are topically administered. In order to test the utility of the system, diclofenac, ketoconazole, hydrocortisone and acetaminophen were applied topically through a synthetic skin surrogate (Strat-M membrane) and the toxicity results were compared to those of acute drug exposure from systemically applying the compounds. The heart–liver system was successful in predicting the effects for both cardiac and liver functions changes due to the compounds. The difference in the concentrations of drugs applied topically compared to systemically indicates that the barrier properties of the skin surrogate were efficient. One important advantage of this heart–liver system was the capability of showing differential effects of acute and chronic drug exposure which is necessary as part of the International Conference in Harmonisation (ICH) tri-partate guidelines. In conclusion, this work indicates a promising heart–liver body-on-a-chip system that can be used for the assessment of potential drug toxicity from dermal absorption as well as evaluate transport dynamics through the skin in the same system.